2020
DOI: 10.1111/bjd.19480
|View full text |Cite
|
Sign up to set email alerts
|

Infantile bullous pemphigoid following serogroup B meningococcal vaccination

Abstract: DEAR EDITOR, A 5-month-old male infant presented with bullous palmoplantar lesions. He had received serogroup B meningococcal vaccination 1 week previously. Physical examination showed tense palmoplantar blisters over an erythematoedematous base (a, b). Direct immunofluorescence showed a linear deposit of IgG and C3 on the basal lamina (c). The patient was diagnosed with infantile bullous pemphigoid (IBP). IBP is an infrequent variant of this blistering disease, which usually affects acral areas. Overall, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…2 It has been reported that BP also occurs following vaccination against influenza, tetanus, and meningococcus vaccines. 4,5 The mechanism of vaccine-induced BP remains to be elucidated.…”
Section: E607mentioning
confidence: 99%
See 1 more Smart Citation
“…2 It has been reported that BP also occurs following vaccination against influenza, tetanus, and meningococcus vaccines. 4,5 The mechanism of vaccine-induced BP remains to be elucidated.…”
Section: E607mentioning
confidence: 99%
“…It has been reported that BP also occurs following vaccination against influenza, tetanus, and meningococcus vaccines. 4 , 5 The mechanism of vaccine‐induced BP remains to be elucidated. The possibility of autoantibody cross‐reaction would be negative because of the lack of structural similarity between vaccines and basement membrane antigens.…”
Section: Figurementioning
confidence: 99%
“… 2 In relation to vaccines, cases of BP have been reported following the administration of vials against tetanus, diphtheria, pertussis, polio, rabies, hepatitis B, rotavirus, pneumococcus, or influenza. 1 , 2 , 3 , 4 , 5 The latency period ranges between one day (or earlier in the case of the pediatric population) 1 and one month following the vaccination. 2 , 4 , 5 The mechanism by which the vaccine induces BP is not well understood, and it is unlikely that a vaccine itself would explain the association, as there are no similarities between the vaccine structure and the basement membrane antigens.…”
mentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 The latency period ranges between one day (or earlier in the case of the pediatric population) 1 and one month following the vaccination. 2 , 4 , 5 The mechanism by which the vaccine induces BP is not well understood, and it is unlikely that a vaccine itself would explain the association, as there are no similarities between the vaccine structure and the basement membrane antigens. 2 One hypothesis that has previously been proposed is that the vaccination may trigger a greater autoimmune response in patients with a significant immunological predisposition, 2 , 4 such as the case of our patient with Alzheimer’s disease, as the vaccine would activate B-cell immunity and, therefore, the production of antibodies, 4 which is the main mechanism by which the lesions of this disease are generated.…”
mentioning
confidence: 99%
“…Infantile BP has been linked to several triggers, including infections, autoimmune diseases, and certain drugs and vaccines such as diphtheria, tetanus, polio, hepatitis B, and meningococcal C vaccines 4 . There has been just one previous report of infantile BP linked to meningococcal B vaccination 5 . In most vaccination‐associated cases, manifestations appear following the first vaccine dose and after a variable amount of time 2 …”
Section: Figurementioning
confidence: 99%